Single and combined effects of carbamazepine and copper on nervous and antioxidant systems of zebrafish (Danio rerio). Issue 10 (2nd June 2020) - Jia, Dantong; Li, Xiuwen; Du, Sen; Xu, Ning; Zhang, Wenming; Yang, Ruyi; Zhang, Yunhai; He, Yide; Zhang, Yongjun
Abstract: Various pollutants co‐exist in the aquatic environment such as carbamazepine (CBZ) and copper (Cu), which can cause complex effects on inhabiting organisms. The toxic impacts of the single substance have been studied extensively. However, the studies about their combined adverse impacts are not enough. In the present study, zebrafish were exposed to environmental relevant concentrations of CBZ (1, 10, and 100 μg/L), Cu (0.5, 5, and 10 μg/L) and the mixtures (1 μg/L CBZ + 0.5 μg/L Cu, 10 μg/L CBZ + 5 μg/L Cu, 100 μg/L CBZ + 10 μg/L Cu) for 45 days, the effects on nervous and antioxidant systems of zebrafish were investigated. The results demonstrated that, in comparison with single exposure group, the combined presence of CBZ and Cu exacerbated the effect of antioxidant system (the ability of inhibition of hydroxyl radicals (IHR), superoxide dismutase (SOD), catalase (CAT) and glutathione S‐transferase (GST)) but not nervous system (Acetylcholinesterase [AChE]). The qPCR results supported the changes of corresponding enzymes activities. Hepatic histopathological analysis verified the results of biomarkers. Our work illustrated that the toxicity of mixed pollutants is very complicated, which cannot simply be inferred from the toxicity of single pollutant, and calls for more co‐exposure experiments to better understanding of the co‐effects of pollutants on aquatic organisms.